COMPARATIVE PHARMACOGNOSTICAL EVALUATION OF COSTUS SPECIOSUS (WILD GINGER) AND ZINGIBER OFFICINALE (GINGER) RHIZOME - Kala, Chandra; Ali, Syed Salman; Chaudhary, Sudhir (International Journal of Current Pharmaceutical Research, 2016)
Objective: Costus speciosus Koen. (Ginger) is an Indian ornamental plant, belonging to family Costaceae. The present research work deals with the establishment of standardization parameter regarding comparative pharmacognostic study between Costus speciosus and Zingiber officinale rhizome. Methods: Macroscopic and microscopic evaluation, physicochemical parameters like ash values, moisture content, extractive value, fluorescence analysis and the preliminary phytochemical investigation was done. Results: The Macroscopic difference was found as an absence of odor and taste in Costus speciosus and presence of pungent and aromatic odor in Zingiber officinale. Oil globule, tracheids, starch granules in Zingiber officinale was found whereas the absence of the same in Costus speciosus rhizome was found in the microscopic evaluation. Fluorescence study also exhibits differences. The presence of saponin, carbohydrate, glycosides in Costus speciosus whereas Zingiber officinale revealed the presence of alkaloids, glycosides, flavonoids and protein. Conclusion: These finding can serve as the basis for Identification and investigation of Costus speciosus and Zingiber officinale rhizome and can also establish the characteristic differentiating features of both.